The Role of ESG-Based Intellectual Capital on Green Accounting and CSR through Good Corporate Governance: A Mixed Method Study in Mining Companies - Sumarni, Sumarni; Ramadhan, Rizky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the direct influence of ESG-Based Intellectual Capital (ESG-IC) on Corporate Social Responsibility (CSR) and Green Accounting (GA), and to assess the mediating role of Good Corporate Governance (GCG) within the operational partners of a major mining company in Indonesia. Employing a Mixed Method Sequential Explanatory design, the research initially used Structural Equation Modeling-Partial Least Squares (SEM-PLS) on data collected from 116 managerial respondents. The quantitative results indicate that ESG-IC significantly and positively influences CSR, GCG, and GA, while GCG also significantly affects both CSR and GA. Crucially, GCG is proven to be a partial mediator in the relationship between ESG-IC and both CSR (H6) and GA (H7). The subsequent qualitative phase, using thematic analysis from in-depth interviews, confirms this statistical finding by revealing that ESG-IC acts as the initiator of sustainability actions, driven by Human and Structural Capital. In contrast, GCG functions as the validator and formalizing mechanism of accountability, which elevates the legal and credible impact of ESG-IC, particularly in Green Accounting practices. This study concludes that optimal sustainability implementation relies on a synergy where the resources from ESG-IC are channeled, formalized, and strictly overseen by robust GCG mechanisms.